Augmented Reality untuk Video Stereoscopic Pencak Silat - Citra Devi Murdaningtyas; Firza Nugra Satriaputra; Novita Astin (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2021)
There are many kinds of martial arts in Indonesia, both native martial arts from Indonesia such as pencak silat to various imported products from other countries such as karate, judo to capoeira. There are many pencak silat college, both in Indonesia and even around the world. One of the most influential martial arts in the history of Indonesian pencak silat is Tapak Suci. Based on survey data to the general public in Indonesia, out of 53 respondents there are only 20 respondents who know the pencak silat Tapak Suci, besides that only 3 respondents know the difference between Pencak Silat Tapak Suci and other martial arts, this is also reinforced by data from respondents who know that the Champ Light Tapak Suci team is only 5.7%. From these problems, a solution was made in the form of